2014
DOI: 10.1007/s13365-014-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy, focal spinal cord lesions and alterations of diffusion tensor imaging (DTI) parameters in asymptomatic virus carriers and patients suffering from human T-lymphotrophic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP)

Abstract: In tropical spastic paraparesis, spinal cord atrophy is a well-known finding in magnetic resonance imaging. But in contrast to histological reports, focal lesions of the spinal cord have only been described in imaging reports in exceptional acute cases. Here, we looked for such focal lesions and for alterations of diffusion tensor imaging parameters of the long fibre tracts in the usual case of a long-standing and slowly progressive disease. We examined 10 symptomatic patients, 11 seropositive, but asymptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
9
2
Order By: Relevance
“…A retrospective study from 1996 to 2007 from two sentinel hospitals from Havana and Matanzas Cuba that registered all lymphoid neoplasms, reported only five ATLL cases [220]. On the contrary, in spite of multiple reports about TSP/HAM in Dominican Republic and Puerto Rico [218,[221][222][223], we could not find a single ATLL case. Although it is not clear which is the most prevalent subtype, HTLV-1 is almost exclusively the one reported [216,220,224,225].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 78%
See 1 more Smart Citation
“…A retrospective study from 1996 to 2007 from two sentinel hospitals from Havana and Matanzas Cuba that registered all lymphoid neoplasms, reported only five ATLL cases [220]. On the contrary, in spite of multiple reports about TSP/HAM in Dominican Republic and Puerto Rico [218,[221][222][223], we could not find a single ATLL case. Although it is not clear which is the most prevalent subtype, HTLV-1 is almost exclusively the one reported [216,220,224,225].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 78%
“…TSP/HAM was first described in the Southern Pacific of Colombia in 1981 as a chronic non-hereditary spastic paraparesis, initially termed Pacific spastic paraparesis [ 508 ], later also observed in the Caribbean islands of Martinique and Jamaica and in HTLV endemic regions of Japan. TSP/HAM seems to be highly prevalent in LA, particularly for Afro-descendants, but also for mestizo and Caucasian populations [ 223 , 249 , 351 , 448 , 449 , 452 , 453 , 454 , 455 , 461 , 464 , 472 , 509 ]. Likewise, infective dermatitis, strongyloidiasis and many other dermatological, oral, ocular and neurological complications are usually found co-presenting with ATLL or TSP/HAM, or independent of those diseases in HTLV endemic regions of Peru, Chile and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a large percentage of HTLV-1-infected subjects who do not meet the criteria for definite HAM/TSP suffer from symptoms or diseases related to this viral infection [8,9,[27][28][29]. Spinal cord injury is the main cause of bladder dysfunction in patients with definite HAM/TSP [30]. However, a high percentage of patients without definite HAM/ TSP also present urinary complaints characterized mainly by nocturia, urgency, incontinence and a feeling of incomplete bladder emptying [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the spinal cord, inflammatory myelitis is characterized by decreased FA values in the region of T2‐weighted lesions, with increased FA values seen at lesion boundaries 15 . Vilchez et al., 11 in addition to conventional MRI of the cervical cord and thoracolumbar spine, investigated DTI parameters in the evaluation of patients with definite HAM and HTLV‐1 carriers. These authors identified significant correlations exclusively between reduced FA in dorsal fiber and neurological findings.…”
Section: Discussionmentioning
confidence: 99%